New signcryption algorithm for secure communication of ad hoc networks - ZHANG Chuan-rong1; ZHANG Yu-qing1; LI Fa-gen3; XIAO Hong2 (Tongxin xuebao)
At first, a new identity based signcryption algorithm was proposed; its security and efficiency were analyzed. As a result, its provable security in the random oracle model is proved; compared with the previous identity based sign- cryption algorithms, the new algorithm has lower computation cost and communication overhead. It is very suitable for secure communication protocols of key management and secure routing in ad hoc networks. Finally, for showing the ap- plication methods and significance of new identity based signcryption algorithm in ad hoc networks, a share refreshing protocol of a serve node’s system private key in threshold key management of ad hoc networks is given.